2017
DOI: 10.4236/tel.2017.73047
|View full text |Cite
|
Sign up to set email alerts
|

Have the Special Economic Zones Succeeded in Attracting FDI?—Analysis for India

Abstract: The introduction of Special Economic Zones (SEZs) in India has injected hope for augmented economic growth in recent future. The motive behind establishment of SEZs was mainly to fuel rapid economic growth, provide world class infrastructure and employment, promote exports, increase foreign exchange reserves and attract more Foreign Direct Investment (FDI). The main objective of the paper is to investigate whether the enactment of SEZ policies had any impact on inflow of FDI among Indian states. This is tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…Moberg (2015) affirmed that the FEZ is the second-best solution (the best would be a completely free market, without any local constraints) for the country to integrate into the international division of labor without trade liberalization for the whole economy. Chakraborty, Gundimeda and Kathuria (2017) pointed out that FEZ would benefit the host country by attracting foreign direct investment, creating employment, increasing exports and fostering its economic ties through technology transfer and the use of local resources. Xie, Swerts and Pumain (2018) claimed that investments in FEZs could facilitate cluster development, strengthen urban development and promote workers and highly skilled professionals' economic well-being.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moberg (2015) affirmed that the FEZ is the second-best solution (the best would be a completely free market, without any local constraints) for the country to integrate into the international division of labor without trade liberalization for the whole economy. Chakraborty, Gundimeda and Kathuria (2017) pointed out that FEZ would benefit the host country by attracting foreign direct investment, creating employment, increasing exports and fostering its economic ties through technology transfer and the use of local resources. Xie, Swerts and Pumain (2018) claimed that investments in FEZs could facilitate cluster development, strengthen urban development and promote workers and highly skilled professionals' economic well-being.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some empirical studies have established a positive impact of SEZs on FDI. For instance, Chakraborty et al (2017) in their study on the impact of SEZ policies on FDI inflows in Indian states found that the SEZ policy induced more FDI inflows. Likewise, Graham (2004) found that SEZs were a necessary first step in China's emergence as the largest developing host nation for FDI, especially during the 1980s.…”
Section: Empirical Underpinningsmentioning
confidence: 99%
“…Results from the world's second most populous country also show promise. Within India, FDI inflows are higher in states with higher per capita income (market size), coastal infrastructure (nearness to ports) and urbanisation (Chakraborty, Gundimeda, & Kathuria, 2017). Their research shows that the most successful Indian SEZs are located in cities or nearby areas where there is ample access to road networks, seaports and airports for easy cargo transportation.…”
Section: Scientific Literature Reviewmentioning
confidence: 99%